the study of the relationship between the neuromuscular coordination of the lower limbs and the effectiveness of the direct free kick shot in soccer - Boulabeiz , Abdessamed; Zaaboub, Djame (sports creativity, 2025)
The study aimed to fin the relationship between the neuromuscular coordination of the lower limbs, and the effectiveness of direct free kicks shot among soccer players, where the researchers selected the study sample(usm.berrahal u19)intentionally, and following the approach descriptive, and using tests as a tool to collect data, the first test is the coordination test (eye-feet),the second is the test of ropes to measure the level of shooting accuracy, in addition the test of flamingo to measure the general balance, and the last test is the shooting to the farthest possible distance, finally the researchers reached the aim of the study and the main hypothesis that say: there is a statistically significant relationship between the neuromuscular coordination of the lower limbs and the effectiveness of direct free kicks shot among soccer players